Quantum tailoring of electronic properties in covalently functionalized graphene: application to ammonia gas detection. Issue 55 (15th December 2022) - Dammak, A.; Raouafi, F.; Cavanna, A.; Rudolf, P.; di Caprio, D.; Sallet, V.; Madouri, A.; Jancu, J. M.
Abstract : Quantum tailoring of NH3 gas detection on 4SBD modified graphene. Abstract : Functionalized graphene offers great potential in the field of rapid detection of gases at room temperature. We performed first-principles calculations to study the suitability of 4-sulfobenzenediazonium salts (4SBD) as bandgap modifier in graphene. The signature of unpaired spins is evidenced near the Fermi level owing to the symmetry breaking of graphene sublattices. 4SBD-chemisorbed on graphene is found to be electronically sensitive to the presence of ammonia NH3 with increasing gas concentration.